2015
DOI: 10.1128/ec.00129-15
|View full text |Cite
|
Sign up to set email alerts
|

MIG1Regulates Resistance of Candida albicans against the Fungistatic Effect of Weak Organic Acids

Abstract: bCandida albicans is the leading cause of fungal infections; but it is also a member of the human microbiome, an ecosystem of thousands of microbial species potentially influencing the outcome of host-fungal interactions. Accordingly, antibacterial therapy raises the risk of candidiasis, yet the underlying mechanism is currently not fully understood. We hypothesize the existence of bacterial metabolites that normally control C. albicans growth and of fungal resistance mechanisms against these metabolites. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 51 publications
2
32
0
Order By: Relevance
“…Secretion of the mouse cathelicidin-related antimicrobial peptide (mCRAMP) in the GI lumen was recently shown to play an important role in controlling C. albicans colonization in the mouse GI tract (Fan et al, 2015); however no significant correlation between mouse GI tract fitness and mCRAMP resistance was observed (Figure 4B). Microbiota-derived weak organic acids, such as acetic and lactic acid, were shown to be fungistatic and proposed to contribute to colonization resistance against C. albicans in the mouse GI tract (Cottier et al, 2015b), however Candida strains and species displaying the highest competitive fitness in the mouse GI tract did not show a significant increase in acetic acid or lactic acid resistance (Figures 4C,D). An important feature of gut commensal microbes is their ability to survive in the presence of bile (Strati et al, 2016), but GI fitness was uncorrelated to resistance to ox bile or bile salts (Figures 4E,F).…”
Section: Resultsmentioning
confidence: 99%
“…Secretion of the mouse cathelicidin-related antimicrobial peptide (mCRAMP) in the GI lumen was recently shown to play an important role in controlling C. albicans colonization in the mouse GI tract (Fan et al, 2015); however no significant correlation between mouse GI tract fitness and mCRAMP resistance was observed (Figure 4B). Microbiota-derived weak organic acids, such as acetic and lactic acid, were shown to be fungistatic and proposed to contribute to colonization resistance against C. albicans in the mouse GI tract (Cottier et al, 2015b), however Candida strains and species displaying the highest competitive fitness in the mouse GI tract did not show a significant increase in acetic acid or lactic acid resistance (Figures 4C,D). An important feature of gut commensal microbes is their ability to survive in the presence of bile (Strati et al, 2016), but GI fitness was uncorrelated to resistance to ox bile or bile salts (Figures 4E,F).…”
Section: Resultsmentioning
confidence: 99%
“…The involved pathways differ between species. For example, CaMig1, a transcription factor associated with glucose repression, was discovered as a central regulator of weak organic acid like lactic, acetic, propionic, and butyric acid resistance in C. albicans, however, it is only active in the presence of glucose [112]. In fact, glucose is limited in the vaginal tract [113], making this glucose-dependent response unlikely to contribute to lactic acid resistance in the vaginal environment.…”
Section: Lactic Acidmentioning
confidence: 99%
“…In C. albicans , response and tolerance to acetic acid was found to be largely dependent on the transcription factor Mnl1, which controlled a substantial percentage of the genes activated by the acid (Ramsdale et al 2008). More recently, it was also shown that the glucose-regulated transcription factor Mig1 plays an important role in providing protection against the toxic effect exerted by acetic acid and other organic acids in acidic environments (Cottier et al 2015b). No significant homolog of ScHaa1 was found in C. albicans , but in C. glabrata the ORF CAGL0L09339g encodes a protein with similarity to ScHaa1, particularly in the N-terminal region.…”
mentioning
confidence: 99%